Census of Population and Housing, 1980 (United States): Summary Tape File 3C ([Verlag nicht ermittelbar], 1984)
This data collection is a component of Summary Tape File (STF) 3, which consists of four sets of data containing detailed tabulations of the nation's population and housing characteristics produced from the 1980 Census. The STF 3 files contain sample data inflated to represent the total United States population. The files also contain 100-percent counts and unweighted sample counts of persons and housing units. All files in the STF 3 series are identical, containing 321 substantive data variables organized in the form of 150 "tables," as well as standard geographic identification variables. Population items tabulated for each person include demographic data and information on schooling, ethnicity, labor force status, and children, as well as details on occupation and income. Housing items include size and condition of the housing unit as well as information on value, age, water, sewage and heating, vehicles, and monthly owner costs. Each dataset provides different geographic coverage. STF 3C consists of one nationwide data file containing information about all states. It contains summaries for the United States, census regions, census divisions, states, standard consolidated statistical areas (SCSAs), standard metropolitan statistical areas (SMSAs), urbanized areas, counties, places of 10,000 or more, congressional districts, and minor civil divisions (MCDs) of 10,000 or more in Connecticut, Maine, Massachusetts, Michigan, New Hampshire, New Jersey, New York, Pennsylvania, Rhode Island, Vermont, and Wisconsin. The Census Bureau's machine-readable data dictionary for STF 3 is also available through CENSUS OF POPULATION AND HOUSING, 1980 [UNITED STATES]: CENSUS SOFTWARE PACKAGE (CENSPAC) VERSION 3.2 WITH STF4 DATA DICTIONARIES (ICPSR 7789), the software package designed specifically by the Census Bureau for use with the 1980 Census data files.